The Fracture Process of the Mortar Pump’s Work Surfaces with Abrasive Particles - Kaczynski, Roman; ., Oleksiyvasyliev; Vasyliev, Ievgen (International Journal of Engineering and Technology, 2018)
Using the example of a mortar pump with a flow-through plug the authors of the article offer a mathematical model of the fracture process of the mortar pumpâ€™s work surfaces under the action of abrasive sand particles. The influence of different factors, material properties and conditions of wearing on the wear rate are analyzed in this research paper. Â Â